Variation in the characteristics of groundwater in Jalawla sub-district and its investment - Ahmed, Ismail Taha; Ahmed, Joan Samin (Al-Adab Journal, 2023)
The study area extends from 44°59'22.68"E longitude to 45°16'15.52"E ​​longitude and from latitude 34°11'21.3"N north to a circle It is 34°28'49.79"N wide and has an area of ​​467 km2 in the northern part of Diyala Governorate. Geologically, the study area covers the sediments of the Tertiary and Quaternary periods. The formations of the Tertiary period included the Bay Hassan Formation, which we observe in the northern parts of the city, some western and central sites, and the Muqdadiyah formation, which occupies 44.52%. Which is concentrated in the eastern and central parts of the study area and includes the Quaternary era on the flood plains and sediments of multiple origin, which occupy 55.48%. It is one of the most important underground reservoirs in the study area. The nature of the climate, which played a major role in the climatic balance, was the semi-arid climate, which led to a water deficit in all months of the year in the two stations of Khanaqin and Tuz Khurmatu. The study showed that the soil in the study area consisted mainly of two types of calcareous desert soils, whose area is 94.55 km2 and their percentage is 21.51%. The second type is dry limestone soil, which is poorly textured soil and its area is 344.95 km2 and its percentage reaches 78.49% of the total area of ​​the area. As for the natural vegetation, its spread is near the cultivated areas and near the irrigation and drainage projects, which revealed to us the presence of various types of vegetation cover in the study area.